1995
DOI: 10.1016/0045-6535(95)00158-5
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the photolytic degradation of octachlorodibenzofuran (OCDF) and octachlorodibenzo-p-dioxin (OCDD)

Abstract: A comparative study of the photolytic degradation of octachlorodibenzofuran (OCDF) and octachlorodibenzo-p-dioxin (OCDD). Wagenaar, W.J.; Boelhouwers, E.J.; de Kok, H.A.M.; Groen, C.P.; van Houtenlaan, C.J.; Govers, H.A.J.; Olie, K.; de Gerlache, J.; de Rooij, C.G. Published in: Chemosphere DOI:10.1016/0045-6535(95)00158-5 Link to publication Citation for published version (APA):Wagenaar, W. J., Boelhouwers, E. J., de Kok, H. A. M., Groen, C. P., van Houtenlaan, C. J., Govers, H. A. J., ... de Rooij, C. G. (19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…A first hypothesis could be that PCDD/Fs are more exposed to UVlight in vegetation than in soil, which would mean a degradation by UV-light of the higher chlorinated congeners on vegetation samples. However, Wagenaar et al (1995) showed that OCDF is much more sensitive to UV-light degradation than OCDD, and the ratio between OCDF and OCDD is approximately the same in soil than in vegetation samples. Consequently, UV-light degradation seems not be a suitable explanation.…”
Section: Discussionmentioning
confidence: 94%
“…A first hypothesis could be that PCDD/Fs are more exposed to UVlight in vegetation than in soil, which would mean a degradation by UV-light of the higher chlorinated congeners on vegetation samples. However, Wagenaar et al (1995) showed that OCDF is much more sensitive to UV-light degradation than OCDD, and the ratio between OCDF and OCDD is approximately the same in soil than in vegetation samples. Consequently, UV-light degradation seems not be a suitable explanation.…”
Section: Discussionmentioning
confidence: 94%
“…It was also especifically shown for the octachlorinated congeners (Wagenaar et al 1995). Because of the extremely high K oc of PCDD/Fs, soils with a high content of organic matter should be characterized by high PCDD/F concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon can be explained by the suggestion that the sunlight photolysis rates of PCDFs in nature water are enhanced by indirect or sensitized photoreactions of chemicals naturally occurring in water (Dung et al, 1994), and PCDFs are photochemically less stable than PCDDs (Wagenaar et al, 1995).…”
Section: R E S U L T S a N D Discussionmentioning
confidence: 99%